2018
DOI: 10.1080/1828051x.2017.1422154
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farmers’ business strategies in Central and Eastern Europe based on evidence from Lithuania, Poland and Slovenia

Abstract: To evaluate market-oriented strategic decision-making by farmers in Central and Eastern Europe (CEE) farm development paths of dairy farmers in Slovenia, Poland and Lithuania were analysed. The influence of internal strengths and weaknesses, external opportunities and threats, and farmer goals on strategic choices and performance were explored. Principal component, hierarchical cluster and regression analyses were performed to test the conceptual framework. Seven strategic groups emerged with specific developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…The present study showed this dualisation but also quantified these two tendencies: 46% vs. 26% of producers having high positive and high negative scores respectively on the second dimension. Verhees et al (2018) [13] quantified producers as a function of their strategies of development, but solely regarding specialisation vs. diversification of their activity, 54.3% vs 15.1%…”
Section: Dualisation Of Ideal Future Farm Aspirationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study showed this dualisation but also quantified these two tendencies: 46% vs. 26% of producers having high positive and high negative scores respectively on the second dimension. Verhees et al (2018) [13] quantified producers as a function of their strategies of development, but solely regarding specialisation vs. diversification of their activity, 54.3% vs 15.1%…”
Section: Dualisation Of Ideal Future Farm Aspirationsmentioning
confidence: 99%
“…Similar relationships between characteristics of the farm and current or desired models of farming were observed by others. For Central and Eastern Europe, Verhees et al (2018) [13] showed that land was the most important factor in developing a specific farming strategy. In France, Hostiou et al (2015) [21] observed that intensified farms with higher technology equipment sometimes employed more workers, and were the farms with significantly higher agricultural area, percentage of corn silage, number of cows and milk quota.…”
Section: Production Factorsmentioning
confidence: 99%
See 3 more Smart Citations